Implementation of City Ordinance in a Highly Urbanized City: Inputs to Public Safety and Security - Gile, Wilzar L.; Plata, Nilmar P.; Anselmo, Charlie T.; Mosqueda, Riando D. (International Journal of Multidisciplinary: Applied Business and Education Research, 2025)
This study assessed the implementation of city ordinances in a highly urbanized city in the Philippines and their implications for public safety and security. A quantitative descriptive research design was employed, with data collected from 149 respondents, comprising police officers, barangay officials, and community residents, using a self-administered survey questionnaire. The findings revealed a strong consensus among the three groups, who rated the implementation of community service, issuance of violation receipts, filing of cases, and reporting procedures as "Highly Implemented." Common violations, such as curfew breaches, public smoking, and drinking in public, were identified as persistent challenges. ANOVA results confirmed no significant differences in the assessments of the three groups, indicating a unified perception of ordinance enforcement’s effectiveness. This study highlights the importance of collaborative efforts among law enforcement, local officials, and the community in maintaining public order. Recommendations include developing an integrated digital management system to strengthen documentation, reporting, and public engagement, as well as fostering continuous collaboration with local communities and organizations to enhance trust and actively participate in upholding public safety. The findings contribute to the understanding of effective urban governance strategies and align with the principles of the "Safe City" framework, emphasizing the significance of data-driven, technology-enabled approaches in ensuring sustained public safety and security in complex urban environments.